Development of Project-Based Learning Modules on the Subject of Chemical Equilibrium - Purba, Jamalum; Sembiring, Bilham Aditia (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2023)
This study aims to determine the feasibility of project-based learning modules on the subject of chemical equilibrium in accordance with BNSP requirements, which include: (1) Content Feasibility, (2) Presentation Feasibility, (3) Language Eligibility, and (4) Graphic Feasibility, this research also aims to determine student responses to project-based learning modules on the subject of chemical equilibrium. This research was developed using the Research & Development (R&D) method using the ADDIE development model. This research was conducted at Medan State University (UNIMED) and SMA Negeri 6 Binjai. The results of this study indicate that through the development of project-based learning modules on the subject of chemical equilibrium: (1) Average content eligibility by lecturers is 3.7 and by teachers 3.8., (2) Average eligibility presentation by lecturers is 3, 6 and by the teacher 3.7., (3) The average of language proficiency by the lecturer is 3.5 and by the teacher 3.7., (4) The average graphic proficiency by the lecturer is 3.9 and by the teacher 3.8. And the average result of student responses is 3.73. This means that the learning module that has been developed is feasible and does not need to be revised.